Building micro service for user engagement - Sharma, Devansh; Anandan, R; Manikandan, A; Narayanan, Kumar; Swaraj Paul, C (International Journal of Engineering and Technology, 2018)
The emails that are being sent today are done manually through the use of email providers like Gmail, Yahoo, Hotmail etc. with a copy paste mechanism of the same message. This requires more human resource and time. The system now being developed will be able to send the emails to thousands number of user without any copy-paste mechanism in very less time and with great accuracy handling all errors, if occurs, through the use of Amazon web services & Google Cloud services. Thus, the messages received by every user will be unique instead of the same message being sent to all. The email micro service will be responsible for handling out all the essential needs, verification & validation, automation, clean code and follows a proper SDLC as per current industry standards. The track ability feature will also be provided to track all the emails that are being sent to the users. Thus, the automation will be done and will save a lot of human resource and time.Â Â